2019
DOI: 10.24251/hicss.2019.594
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Digital Transformation in Manufacturing: Development of a Research Agenda

Abstract: Digital Transformation (DT) is expected to have a massive impact on different branches and even societies. In the manufacturing industry, value creation processes change as information and communication technologies merge with production processes. The change may enable efficiency gains and new business models. However, many firms still struggle to drive their digital transformation forward. To understand the barriers which hinder or even stop DT is essential for the successful transformation. Our study aims a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 85 publications
(111 citation statements)
references
References 47 publications
1
56
0
4
Order By: Relevance
“…The questionnaire was created based on the existing theory of barriers to digital transformation (Vogelsang, Liere-Netheler, Packmohr, & Hoppe, 2019) and adjusted to the setting in higher education. We used further existing research to complement the survey questions.…”
Section: Research Methods and Samplementioning
confidence: 99%
“…The questionnaire was created based on the existing theory of barriers to digital transformation (Vogelsang, Liere-Netheler, Packmohr, & Hoppe, 2019) and adjusted to the setting in higher education. We used further existing research to complement the survey questions.…”
Section: Research Methods and Samplementioning
confidence: 99%
“…Thus, DT is a continuous process based on several digital innovations that build upon each other to reach transformative scale. This continuous process is not limited to integrating various digital resources -it includes adapting organizational management [15,27] of cultural, technical and individual barriers [34], capability building processes [20,29], and alignment of novel and existing resources. Effectively combining existing digital and non-digital resources is therefore critical for achieving successful DT.…”
Section: Digital Transformationmentioning
confidence: 99%
“…Vogelsang et al, also identified a set of barriers related to the skills and individual profiles of workers in IIoT. The missing skills included the absence of necessary IT skills and appreciation for IIoT, the absence of process compatibility with technical knowledge, and the lack of overall technical appreciation for the role of technology [3].…”
Section: Human Capitalmentioning
confidence: 99%
“…Much of the available empirical literature discuss IIoT in highly developed economies like the United States, the United Kingdom, Australia, Singapore, Hong Kong, and China. This hinders the ability of interested stakeholders in adopting IIoT in many contexts [3] such as limited access to resources, non-specialized human capital and fragmented technological infrastructures; the case of many developing nations. Prior to the implementation of IIoT, stakeholders need to address areas of deficiencies or deal with potential barriers [4].…”
Section: Introductionmentioning
confidence: 99%